Interplay between Inflammation and Cellular Stress Triggered by Flaviviridae Viruses - Valadão, Ana L. C.; Aguiar, Renato S.; de Arruda, Luciana B. (Frontiers in Microbiology, 2016)
Flaviviruses, from Flaviviridae virus family, comprises several human pathogens, including Dengue, Zika, Yellow Fever, West Nile and Japanese Encephalitis viruses. Those are enveloped, single-stranded positive sense RNA viruses, and replicate mostly in intracellular compartments associated to endoplasmic reticulum (ER) and Golgi complex. Virus replication results in abundant viral RNAs and proteins, which are recognized by cellular mechanisms evolved to prevent virus infection, resulting in inflammation and stress responses. Virus RNA molecules are sensed by Toll-like receptors (TLRs), RIG-I-like receptors (RIG-I and MDA5) and RNA-dependent protein kinases (PKR), inducing the production of inflammatory mediators and interferons. Simultaneously, the synthesis of virus RNA and proteins are distinguished in different compartments such as mitochondria, ER and cytoplasmic granules, triggering intracellular stress pathways, including oxidative stress, UPR pathway, and stress granules assembly. Here, we review the new findings that connect the inflammatory pathways to cellular stress sensors and the strategies of Flaviviridae members to counteract these cellular mechanisms and escape immune response.